Preoperative individual-target transcranial magnetic stimulation demonstrates an effect comparable to intraoperative direct electrical stimulation in language-eloquent glioma mapping and improves postsurgical outcome: A retrospective fiber-tracking and electromagnetic simulation study - Li, Sanzhong; Mu, Yunfeng; Rao, Yang; Sun, Chuanzhu; Li, Xiang; Liu, Huan; Yu, Xun; Yan, Xiao; Ding, Yunxia; Wang, Yangtao; Fei, Zhou (Frontiers in Oncology, 2023)
Background Efforts to resection of glioma lesions located in brain-eloquent areas must balance the extent of resection (EOR) and functional preservation. Currently, intraoperative direct electrical stimulation (DES) is the gold standard for achieving the maximum EOR while preserving as much functionality as possible. However, intraoperative DES inevitably involves risks of infection and epilepsy. The aim of this study was to verify the reliability of individual-target transcranial magnetic stimulation (IT-TMS) in preoperative mapping relative to DES and evaluate its effectiveness based on postsurgical outcomes. Methods Sixteen language-eloquent glioma patients were enrolled. Nine of them underwent preoperative nTMS mapping (n=9, nTMS group), and the other seven were assigned to the non-nTMS group and did not undergo preoperative nTMS mapping (n=7). Before surgery, online IT-TMS was performed during a language task in the nTMS group. Sites in the cortex at which this task was disturbed in three consecutive trials were recorded and regarded as positive and designated nTMS hotspots (HSnTMS). Both groups then underwent awake surgery and intraoperative DES mapping. DES hotspots (HSDES) were also determined in a manner analogous to HSnTMS. The spatial distribution of HSnTMS and HSDES in the nTMS group was recorded, registered in a single brain template, and compared. The center of gravity (CoG) of HSnTMS (HSnTMS-CoG)-based and HSDES-CoG-based diffusion tensor imaging-fiber tracking (DTI-FT) was performed. The electromagnetic simulation was conducted, and the values were then compared between the nTMS and DES groups, as were the Western Aphasia Battery (WAB) scale and fiber-tracking values. Results HSnTMS and HSDES showed similar distributions (mean distance 6.32 ± 2.6 mm, distance range 2.2-9.3 mm, 95% CI 3.9-8.7 mm). A higher fractional anisotropy (FA) value in nTMS mapping (P=0.0373) and an analogous fiber tract length (P=0.2290) were observed. A similar distribution of the electric field within the brain tissues induced by nTMS and DES was noted. Compared with the non-nTMS group, the integration of nTMS led to a significant improvement in language performance (WAB scores averaging 78.4 in the nTMS group compared with 59.5 in the non-nTMS group, P=0.0321 < 0.05) as well as in brain-structure preservation (FA value, P=0.0156; tract length, P=0.0166). Conclusion Preoperative IT-TMS provides data equally crucial to DES and thus facilitates precise brain mapping and the preservation of linguistic function.